Glutamine Supplementation Effects on Reducing Inflammation in The Ileum of Acute and Chronic Diarrhea Rats Induced by Enteropathogenic Escherichia coli - Deddy Satriya Putra; Fadil Oenzil; Eryati Darwin; Hafni Bachtiar; Tofrizal Tofrizal (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Glutamine, a non-essential amino acid, is the main fuel in the gastrointestinal mucosa. It is thought to protect the intestinal mucosa against local or systemic injury from diarrhea. This study aimed to determine the relationship between glutamine supplementation and ileum histopathology in acute and chronic diarrhea rats induced by enteropathogenic Escherichia coli (EPEC).METHODS: A randomized post-test only control group design was conducted. Thirty Rattus norvegicus Wistar strain were divided into 5 groups: one negative control group, two acute, and two chronic diarrhea groups. All four diarrhea groups were induced by EPEC at a dose of 108 CFU/mL. One acute and one chronic groups were supplemented with glutamine at a dose of 810 mg/200 g body weight for 14 days. While the other two diarrhea groups were not treated. The intestinal histopathology of each group was assessed and the level of inflammation was classified.RESULTS: Significant differences in inflammation levels were found among the groups (p<0.05). The highest inflammation level was observed in the acute diarrhea group without glutamine supplementation. Inflammation levels of both acute and chronic diarrhea with glutamine supplementation groups were significantly lower than the inflammation levels of acute and chronic diarrhea without glutamine supplementation groups.CONCLUSION: Supplementation of glutamine reduces the level of inflammation and leads to the histopathological improvement of the rat’s ileum.KEYWORDS: enteropathogenic Escherichia coli, glutamine, gastrointestinal tract, histopathology, ileum